Comparative analysis of management practices and end-users' desired breeding traits in the miracle plant [Synsepalum dulcificum (Schumach & Thonn.) Daniell] across ecological zones and sociolinguistic groups in West Africa - Dèdéou A. Tchokponhoué; Enoch G. Achigan-Dako; Sognigbé N'Danikou; Daniel Nyadanu; Rémi Kahane; Alfred O. Odindo; Julia Sibiya (BMC, 2021)
Abstract Background Understanding end-users' preferred breeding traits and plant management practices is fundamental in defining sound breeding objectives and implementing a successful plant improvement programme. Since such knowledge is lacking for Synsepalum dulcificum, a worldwide promising orphan fruit tree species, we assessed the interrelationships among socio-demography, ecology, management practices, diversity and ranking of desired breeding traits by end-users of the species (farmers, final consumers and processing companies) in West Africa. Methods Semi-structured interviews, field-visits and focus groups were combined to interview a total of 300 farmers and final consumers belonging to six sociolinguistic groups sampled from three ecological zones of Benin and Ghana. One processing company in Ghana was also involved. Data collected included socio-demographic characteristics; crop management systems and practices; and preferences of farmers, final consumers and processing companies and ranking of breeding traits. Data were analysed using descriptive statistics, independence, and non-parametric tests, generalized linear models, multi-group similarity index and Kendall's concordance coefficient. Results Men (86.33% of respondents) were the main holders of S. dulcificum in the study area. The three most frequent management practices observed in the species included weeding, fertilization and pruning, which were applied by 75.66%, 27.33% and 16.66% of respondents, respectively. The management intensity index varied significantly across ecological zones, sociolinguistic groups, and instruction level (p < 0.001) but was not affected by gender (p > 0.05). General multigroup similarity indices ( C S T $$ C_{S}^{T} $$ ) for farmer-desired traits, on one hand, and final consumer-desired traits, on the other hand, were high across ecological zones ( C S T $$ C_{S}^{T} $$ ≥ 0.84) and sociolinguistic groups ( C S T $$ C_{S}^{T} $$ > 0.83). Nevertheless, respondents from the Guineo-Congolian (Benin) and the Deciduous forest (Ghana) zones expressed higher agreement in the ranking of desired breeding traits. Preference for breeding traits was 60% similar among farmers, final consumers, and processors. The key breeding traits desired by these end-users included in descending order of importance big fruit size, early fruiting, high fruit yielding (for farmers); big fruit size, high fruit miraculin content, fruit freshness (for final consumers); and high fruit miraculin content, big fruit size, high fruit edible ratio (for processing companies). Conclusion This study revealed stronger variations in current management practices across ecological zones than across sociolinguistic groups. A high similarity was shown in end-users' preferences for breeding traits across the study area. Top key traits to consider in breeding varieties of S. dulcificum to meet various end-users' expectations in West Africa include fruit size and fruit miraculin content. These results constitute a strong signal for a region-wide promotion of the resource.